PENGARUH KEPEMIMPINAN, PENGEMBANGAN SUMBER DAYA MANUSIA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN CILEUNYI, KABUPATEN BANDUNG, PROVINSI JAWA BARAT - Ambarawati, Ayu (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT In measuring performance based on leadership, development and job satisfaction in Cileunyi District, Bandung Regency, West Java. experienced several obstacles. Based on this background the author takes the title: The Effect of Leadership, Human Resource Development and Job Satisfaction on Employee Performance of Cileunyi District Offices, Bandung Regency, West Java. “ The purpose of this study was to determine the effect of leadership, human resource development and job satisfaction on performance in Cileunyi District, Bandung Regency, West Java. both partially and simultaneously. Partially Leadership Variables (X1) have a positive and significant effect on employee performance. This is indicated by the regression coefficient of 0.233. Whereas for tcount (3,953)> t table (1,697) and sign. (0,001) <sign α (0,05). Increasing leadership, the performance of employees in the Cileunyi District Office, Bandung Regency, West Java. increasing too. Variable Human Resource Development (X2) partially has a positive and significant effect on employee performance (Y). This is indicated by the regression coefficient value of 0.295. Whereas for tcount (2,647)> t table (1,697) and sign (0,014) <sign α (0,05. Increasingly Human Resources Development then the performance of Employees in Cileunyi Subdistrict Office, Bandung Regency, West Java. Job satisfaction variables, (X3) partially have a positive and significant effect on employee performance.This is indicated by the regression coefficient of 0.528, while for the value of t count (4.802)> t table (1.697) and sign. (0.000) <sign α (0.05) The increasing specialization of the type of work, the performance of employees in the Cileunyi Subdistrict Office, Bandung Regency, West Java has also increased, in the feasibility test of the model that this study can be continued in analyzing the influence of Leadership (X1), Human Resource Development (X2) and Employee Satisfaction (X3), towards performance (Y). This is indicated by the Fcount value (284,486)> Ftable (2,98 and sign. (0,000) <sign α (0,05). Increasing Leadership an (X1), Human Resource Development Jurnal MSDA/Vol. 6, No. 2/ Desember 2018 195 – 214196(X2) and employee job satisfaction then employee performance in Cileunyi District Office, Bandung Regency, West Java. increasing too. Some suggestions that can be used as input in Cileunyi District, Bandung Regency, West Java. is to improve the leadership system such as giving authority, the role of work, delegation of employee authority, giving work motivation or directing employees. Keywords: leadership, human resources development, work satisfaction, performance